Neurodevelopmental outcomes of premature infants with bronchopulmonary dysplasia - Gallini, F.; Arena, R.; Stella, G.; Frezza, S.; Maggio, L. (Acta Biomedica Atenei Parmensis, 2014)
Bronchopulmonary dysplasia (BPD) is a chronic lung disorder common among very preterm infants affecting significantly not only mortality and morbidity but also neurodevelopmental outcomes. This review aims to identify the short and long-term neurodevelopmental outcomes of infants with BPD, considering that the new definition of BPD allows to relate severity of BPD with greater risk of developmental delay.